The implementation of fire safety management at Heritage Museums, Georgetown, Penang / Nur Amirah Adilah Hamim and Lilawati Ab Wahab - Adilah Hamim, Nur Amirah; Ab Wahab, Lilawati (2020)
Heritage museums are known as being over 50 years old and designed with distinct architectural features of their period. Fire threatens all structures and its impact can be devastating not only for human beings but also especially for heritage museums in economic terms. The loss of property that forms part of an irreplaceable cultural resource where architectural and historical integrity can quickly vanish when there is inappropriate protection from fire. The required and responsive implementation of fire safety management should be considered as part of the long-term preservation strategic plan for any heritage museum. The aim of this research is to investigate the most current fire safety management activity at the George Town, Penang Heritage Museum. The objective is to analyse the current implementation of fire safety management at heritage museums in George Town, Penang. In the chosen heritage museums, the data was collected through observations, literature review and interview methods. The finding found a better fire safety protection by providing the best result of fire safety management. From the survey, the heritage museums show a better understanding in fire safety management.